Sistema aquapônico no cultivo do Litopenaeus vannamei e das plantas halófitas Batis marítimas, Salicornia neei e Sesuvium portulacastrum, em diferentes salinidades, em época de baixa pluviosidade no Ceará - Oliveira Neto, Severino Campos (2023)
The present study evaluated the effects of an aquaponic system on the zootechnical performance of marine shrimp (Litopenaeus vannamei), the water quality and the development of halophyte plants Batis maritimes, Salicornia neei and Sesuvium portulacastrum, cultivated in two levels of salinity. Thus, a study was carried out with an experimental design consisting of four treatments, salinity 40 ppm without aquaponics (SS40), salinity 15 ppm without aquaponics (SS15), salinity 40 ppm in aquaponics (SA40) and salinity 15 ppm in aquaponics (SA15). Each with four replicates with systematic interleaving. Increasing water salinity reduced dissolved oxygen concentration and water pH. The cultivation system affected the concentration of reactive phosphorus and sedimentable solids in the water, so that the tanks with plants had lower concentrations, regardless of the salinity of the water. The productive performance of the halophytes S. portulacastrum and B. maritima differed significantly according to salinity. These plants had higher productive indexes in salinity 15 than in 40. The halophyte S. neei did not have its growth performance affected in both salinity levels. Relative growth rate (RGR) and absolute growth rates (AGR) values, in height, for S. portulacastrum, were statistically different between salinities 15 and 40ppm. The copper concentration in the water in the SS40 tanks was higher than in the SA40 tanks. Shrimp survival, final biomass and productivity were higher in tanks with salinity 40 than those maintained at salinity 15ppm, when the plants were absent. Shrimp kept in tanks with plants did not have improved zootechnical performance. The results indicated that halophyte plants have better growth rates when maintained at salinity 15ppm. In addition, the aquaponic system reduces the concentrations of phosphorus, settleable solids and copper in the water. Although shrimp cultivated in an aquaponic system did not show satisfactory growth rates, aquaponics was efficient in improving water quality in the cultivation of S. portulacastrum and B. maritime.